Jaw elements in Plumulites bengtsoni confirm that machaeridians are extinct armoured scaleworms - Parry, LA; Edgecombe, GD; Sykes, D; Vinther, J (Royal Society, 2019)
Machaeridians are Palaeozoic animals that are dorsally armoured with serialized, imbricating shell plates that cover or enclose the body. Prior to the discovery of an articulated plumulitid machaeridian from the Early Ordovician of Morocco that preserved unambiguous annelid characters (segmental parapodia with chaetae), machaeridians were a palaeontological mystery, having been previously linked to echinoderms, barnacles, tommotiids (putative stem-group brachiopods) or molluscs. Although the annelid affinities of machaeridians are now firmly established, their position within the phylum and relevance for understanding the early evolution of Annelida is less secure, with competing hypotheses placing Machaeridia in the stem or deeply nested within the crown group of annelids. We describe a scleritome of Plumulites bengtsoni from the Fezouata Formation of Morocco that preserves an anterior jaw apparatus consisting of at least two discrete elements that exhibit growth lines. Although jaws have multiple independent origins within the annelid crown group, comparable jaws are present only within Phyllodocida, the clade that contains modern aphroditiforms (scaleworms and relatives). Phylogenetic analysis places a monophyletic Machaeridia within the crown group of Phyllodocida in total-group Aphroditiformia, consistent with a common origin of machaeridian shell plates and scaleworm elytrae. The inclusion of machaeridians in Aphroditiformia truncates the ghost lineage of Phyllodocida by almost a hundred million years.